Augmenting digital monopolies: A corporate financialization perspective on the rise of Big Tech. (April 2023) - Klinge, Tobias J; Hendrikse, Reijer; Fernandez, Rodrigo; Adriaans, Ilke
Building on the notion of corporate financialization, this article analyzes the financial dynamics of the world's largest digital platforms over the period 2000–2020: Alibaba, Alphabet (Google), Amazon, Apple, Meta (Facebook), Microsoft, and Tencent. These "Big Tech" corporations jointly form the infrastructural core of the digital economy. Taking cues from critical media studies and political economy, we probe their financial statements according to three stylized indicators of corporate financialization: (i) expanding financial assets and debt; (ii) augmenting asset structures, with intangible assets in the form of goodwill ballooning alongside tangible capital; and (iii) maximizing shareholder value. Our findings point to commonalities among the 'avantgarde of digital capitalism', where feedback loops between mounting market dominance, data extraction, and above-average profits have been successfully leveraged with key tools of corporate financialization to accelerate Big Tech's infrastructural dominance across economy and society.